Investigating the Quality of Communication between Dentists and Dental Technicians in Iran - Norikhah, Sepehr; Mahdaviifar, Neda; Mashayekhi , Mohammadhasan; Allahyari, Somayeh; Mohamadian, Mohamadmahdi (Journal of Dental School, 2024)
Objectives Well-formed communication between dentists and dental technicians is an important factor for the fabrication of dental prostheses. Numerous articles have highlighted the lack of sufficient communication between dental clinics and laboratories. The present study aimed to assess the communication between dentists and dental technicians in Iran. Methods In this cross-sectional study, a structured questionnaire containing 23 questions about the effectiveness of communication between dentists and dental laboratories was distributed among 154 dental technicians. After data collection, the data were entered into SPSS-24 software and analyzed. Independent t-tests and analysis of variance (ANOVA) were used to analyze the data with independent variables. Results The communication between dental laboratory and clinic had a significant relationship with gender, job characteristics, laboratory location, and laboratory activity in all areas (p-value <0.001). Moreover, 77.3% of the participants perceived their communication as constructive and encouraging, and 50% believed that the dentist followed their opinion after consulting with the dental prosthesis laboratory. Conclusion Training in medical professionalism, as an essential element contributing to communication between dentists and dental technicians, must be included in the dental schools’ curricula.